Respuesta :

Answer:

[tex]x = \frac{-3}{2}[/tex]

Explanation:

Given

2x + y = -3

y = 4x + 6

Required

Find the value of x

2x + y = -3 --- Equation 1

y = 4x + 6  --- Equation 2

Substitute 4x + 6 for y in equation 1.

So, equation 1 becomes

[tex]2x + 4x + 6 = -3[/tex]

[tex]6x + 6 = -3[/tex]

Subtract 6 from both sides

[tex]6x + 6 - 6 = -3 - 6[/tex]

[tex]6x = -9[/tex]

Divide both sides by 6

[tex]\frac{6x}{6} = \frac{-9}{6}[/tex]

[tex]x = \frac{-9}{6}[/tex]

Simplify fraction

[tex]x = \frac{-3}{2}[/tex]

Hence, the value of x is [tex]x = \frac{-3}{2}[/tex]